Pertumbuhan Ekonomi, Kemiskinan, dan Ketimpangan Pendapatan di Kabupaten Banggai Kepulauan Tahun 2018-2023: Economic Growth, Poverty, and Income Inequality in Banggai Regency, 2018-2023 - Amir Buhang; Susianti A Madji (Jurnal Ilmiah Produktif, 2025)
This study analyzes the effect of economic growth and poverty on income inequality in Banggai Kepulauan Regency during the 2018–2023 period. Income inequality is proxied by the Gini Index, economic growth is measured by the growth rate of Gross Regional Domestic Product (GRDP) at constant prices, and poverty is measured by the percentage of the poor population. The data are a six-year time series obtained from publications of the Central Statistics Agency (BPS). The analytical method used is multiple linear regression, complemented by the t-test (partial), F-test (simultaneous), correlation coefficient, and coefficient of determination. The estimation results show the equation:Y = −0.062221 − 0.000695X₁ + 0.025594X₂. Economic growth has a negative but insignificant effect on income inequality, while poverty has a positive and significant effect. Simultaneously, economic growth and poverty significantly affect income inequality. The coefficient of determination (R²) of 0.861 indicates that 86.1% of the variation in income inequality can be explained by changes in economic growth and poverty during the observation period. These findings emphasize the importance of targeted poverty reduction policies and more inclusive growth strategies to strengthen income distribution at the regional level.